Clinical efficacy of Danshen preparation in the treatment of vascular cognitive impairment: A systematic review and meta-analysis - Li, Yunze; Yao, Yangjing; Cao, Xinran; Yi, Nan; Chen, Anqi; Li, Jianjun; Wu, Minghua (Frontiers in Aging Neuroscience, 2023)
Ethnopharmacological relevance Danshen preparations are widely used in the treatment of ischaemic cerebrovascular disease. However, the clinical efficacy of such preparations remains unclear. Consequently, Danshen preparations are used to a lesser extent in vascular cognitive impairment (VCI). Aim of the study In this study, we aimed to systematically assess the clinical efficacy and safety of Danshen preparations in VCI. To this end, we examined and performed a meta-analysis (MA) of the evidence available from randomised controlled trials (RCTs) of Danshen preparations conducted in patients with VCI. Methods We queried the following sources and collected all articles reporting on RCTs of Danshen preparations published prior to December 2021: PubMed, China National Knowledge Infrastructure (CNKI), Wanfang Data, Chongqing VIP Database (CQVIP), and China Biology Medicine (CBM) disc databases. The assessment of treatments that were included in references were performed by RevMan 5.2 software based on guidelines from Cochrane Handbook for Systematic Reviews of Interventions. Results We included a total of 12 RCTs that included data on clinical therapeutic effects. The evaluation criteria included the following: National Institutes of Health Stroke Scale (NIHSS), modified Rankin Scale (mRS), Barthel Index (BI), Mini-Mental State Assessment (MMSE), Montreal Cognitive Assessment (MOCA), Activities of Daily Living Scale (ADL), treatment effect index, and incidence of adverse reaction index. In the included studies, the observation groups included 656 cases and the control groups included 660 cases. The results of the MA were as follows: the mean difference (MD) value after combining the effect size for NIHSS was −2.91, with a 95% confidence interval (CI) of −4.22 to −1.59; the combined effect quantity hypothesis test revealed that Z = 4.33 (p < 0.00001), indicating that the score pertaining to the degree of neurological deficit (NIHSS) in the observation group after treatment was significantly lower than that in the control group. This result reveals that treatment with a Danshen preparation can reduce neurological deficit in VCI patients. The MD value after combining the effect size for mRS was −0.73, with a 95% CI of −0.85 to −0.61; the result of the combined effect quantity hypothesis test revealed that Z = 12.29 (p < 0.00001). These results indicate that the degree of disability was significantly reduced after treatment in the observation group. The MD value after combining the effect size for MMSE was 2.09, with a 95% CI of 0.33–3.84; the result of the combined effect quantity hypothesis test showed that Z = 2.33 (p = 0.02). These results indicate that the cognitive function score (MMSE) of the observation group after treatment was significantly higher than that of the control group and suggests that the cognitive function of VCI patients was improved after treatment with Danshen preparations. The MD value after combining the effect size for ADL was 8.79, with a 95% CI of 3.52 to 14.06; the result of the combined effect quantity hypothesis test indicated that Z = 3.27 (p = 0.001). These results showed that the life ability (ADL scale) scores of patients in the observation group after treatment were significantly higher than those in the control group, and reveals that after treatment with Danshen preparations, patients exhibited significant improvement in life ability. The MD value after combining the effect size for high-sensitivity C-reactive protein (hs-CRP) was −3.21, with a 95% CI of −4.21 to −2.22; the result of the combined effect quantity hypothesis test showed that Z = 6.31 (p < 0.00001), indicating that the hs-CRP level in the observation group was significantly decreased after treatment. The MD value after combining the effect size for interleukin (IL)-6 was −2.95, with a 95% CI of −3.86 to −2.04; the result of the combined effect quantity hypothesis test showed that Z = 6.36 (p < 0.00001). These results showed that the IL-6 level in the observation group was significantly decreased after treatment. Conclusion The existing clinical evidence shows that Danshen preparations exert significant therapeutic effects on VCI patients and can ameliorate inflammatory conditions in these patients. In addition, Danshen preparations are relatively safe.